Total hip arthroplasty for active tuberculosis of the hip - Wang, Yongqing (Springer-Verlag, 2009)
Total hip arthroplasty (THA) has been used as a successful form of treatment in patients with long-standing tuberculosis, but it is unclear whether THA should be performed in patients with current infection. We performed THA in six patients with advanced active tuberculosis of the hip from 2002 to 2006. Tuberculosis was confirmed in all cases by histological examination. All patients were treated with antituberculous medications for at least two weeks followed by thorough debridement and THA. Antituberculous medications were administered postoperatively for at least 12 months. The duration of postoperative follow-up was an average of 49 months. No reactivation of the infection was detected in our series. Using the Harris hip score system, five of the patients were classified as excellent and one as good. THA in advanced active tuberculosis of the hip is a safe procedure providing symptomatic relief and functional improvement. Thorough debridement of infected tissues and postoperative antituberculous therapy are the keys to lowering the potential risk of reactivation of tuberculosis.